Työhyvinvoinnin ulottuvuudet : Hyvinvointivalmennus Hälsan malli - Hämäläinen, Ville-Valtteri (2018)
Hämäläinen, V-V. 2018. Well-being at Work – Hyvinvointivalmennus Hälsa model: Faculty of Sport and Health Sciences, University of Jyväskylä, Master’s thesis, 54 pp., 2 appendices. In this master’s thesis, I wanted to research that whether Hyvinvointivalmennus Hälsa model makes statistically significant differences to workers’ well-being at work during their intervention. One’s own well-being is affected by various different aspects of their lives. One’s daily choices have huge impact of their sense of well-being. Wellbeing at work implies that wellness is also a matter of job environment and other factors that comes to play. In this master’s thesis, we will look at the topic of wellbeing at work in perspectives of physical activity, health behaviors, sick leaves and motivation. Hyvinvointivalmennus Hälsa collected data for this thesis via online surveys from their client before and after the intervention. Sample size of the analysis was 33 (N=33) which are collected from the workers who answered both sets of the surveys. Data was analyzed by using T-test in SPSS program. In this thesis, there were two research questions which include: Is there statistically significant differences between selected variables during intervention? Can we conclude that workers sense of wellbeing at work being increased during intervention? Most positive results were collected from variables that measured workers’ behaviors in physical activity and inactivity. The question about amount of physical activity during a week was statistically significant (p < 0,01). The question that evaluated workers’ sense of physical fitness was also statistically significant (p < 0,05). In addition, the question that evaluated worker’ sitting time during a work day was statistically significant (p < 0,01). On top of that, there were also non-statistically significant results generated from the analysis, such as quality of workers’ lunch meals (p < 0,36), amount of sleep (p < 0,97) and smoking behaviors (p < 0,08). From questions related to physical activity and inactivity, we can conclude Hyvinvointivalmennus Hälsa model successfully increased workers well-being in perspective of physical fitness. This was reflected by the increase in physically active time and the decrease in sitting time of the workers. On the other hand, other variables did not show statistically significant results. To conclude, workers’ well-being was increased in terms of physical fitness. However, further research is needed for more conclusive results based on other factors.